Rich, lavish and trendy: Is lesbian consumers' fashion shopping behaviour similar to gay's? A comparative study of lesbian fashion consumption behaviour in Germany. Issue 4 (14th September 2015) - Braun, Kerstin; Cleff, Thomas; Walter, Nadine
Abstract : Purpose: – The purpose of this paper is to research lesbian fashion consumption in order to draw conclusions on the attractiveness of the lesbian target segment for the fashion industry. So far, lesbians' fashion consumption behaviour has hardly been researched. However, an evinced lesbian stereotype exists which describes doctrinal feminists with an antipathy against consumption in general and fashion shopping in particular. In contrast, gay men have been identified quite contrary as an attractive market segment and marketers have started to particularly target this so-called "dream market". Design/methodology/approach: – First, qualitative semi-structured interviews ( n =18) were conducted to gain first insights into fashion consumption behaviour of lesbians. Second, a quantitative online survey ( n =879) was carried out to generate more detailed findings. Due to the difficult reachability of the homosexual consumer target group, the segment's high online media affinity was used and data collection was conducted through popular German homepages targeted to homosexuals (esp. "queer.de" and "lesarion.de"). The research investigated fashion-consciousness, willingness to pay, brand-affinity, and openness to homosexual marketing. In addition, influencing factors – such as the affinity towards the homosexual scene, career orientation, income, age, status of coming out, and number of inhabitants of the city of residence – have been researched. Findings: – Results prove that lesbians are an equally attractive and financially interesting market segment for fashion marketers as gays. Lesbians have a similarly high fashion-consciousness and willingness to pay, and an even higher brand-affinity – but a lower openness to homosexual marketing than gays. Especially scene-affine femme lesbians with a high-paid professional career are a highly attractive market segment. The study proves the attractiveness of the lesbian target segment for fashion marketing and debunks the myth of the consumption-averse lesbian stereotype. Practical implications: – This paper provides evidence on the attractiveness of the lesbian market segment for the fashion industry. Due to its size and financial attractiveness, the question whether to target lesbians with a specifically adopted marketing mix should be raised. Originality/value: – Research on lesbians' fashion consumption behaviour in general is very scarce and on fashion consumption behaviour in particular is almost non-existent. This study is a first attempt to analyse the major areas of fashion consumption for the German market.